Design, fabrication and measurement of a novel 140 GHz folded waveguide based on SU-8 UV-LIGA technology. (14th July 2015) - Xie, Fuqiang; Ding, Guifu; Zhao, Xiaolin; Cheng, Ping
Abstract: In an RF MEMS field, a folded waveguide is the core structure of a traveling wave tube as a slow-wave structure. 140 GHz is an important atmospheric working window. In this paper, the dispersion property and interaction impedance of a novel 140 GHz folded waveguide were analyzed and simulated using CST Microwave Studio. The beam–wave interaction in the folded waveguide was also simulated, using CST Particle Studio. The output power gain of the folded waveguide reached 24.5 dB at 140 GHz when the emission voltage was 12.7 kV and the emission current was 0.15 A. The simulation process provided structure parameters for further micromachining. Furthermore, to analyze the effect of structure fabrication errors, CST was used to simulate the dispersion and interaction impedance by adding tolerance to some important structure parameters. Finally, multi-step SU-8 UV-LIGA technology was adopted for micromachining the folded waveguide. To ensure adhesion between the SU-8 photoresist and substrate, a thin TiO2 film was formed on the surface of the Ti substrate. In the end, test results showed that the reflection coefficient S 11 and transmission coefficient S 21 were near −28.1 dB and −1.2 dB respectively. Moreover, the output power gain was close to 23 dB at 140 GHz. Good accordance between the simulation and experimental results indicated a reasonable design and high precision of microfabrication by SU-8 UV-LIGA technology.